2005
DOI: 10.1037/0033-3204.42.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating alliance-focused intervention for potential treatment failures: A feasibility study and descriptive analysis.

Abstract: This article describes a pilot study evaluating the feasibility of an approach developed to test the efficacy of a therapeutic intervention (brief relational therapy) for patients with whom it is difficult to establish a therapeutic alliance. In the first phase of the study, 60 patients were randomly assigned to either short-term dynamic therapy (STDP) or short-term cognitive therapy (CBT), and their progress in the first eight sessions of treatment was monitored. On the basis of a number of empirically derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 53 publications
1
64
0
3
Order By: Relevance
“…Some clinically interesting studies were dismissed because they did not match the inclusion criteria, e.g., only two or three respondents were diagnosed with Cluster C [12,13]; pooled outcome for all clusters (e.g., Refs. [14Á16]) or incomplete followup results were presented [17], and the authors, upon request, did not provide more specific data.…”
Section: Methodsmentioning
confidence: 99%
“…Some clinically interesting studies were dismissed because they did not match the inclusion criteria, e.g., only two or three respondents were diagnosed with Cluster C [12,13]; pooled outcome for all clusters (e.g., Refs. [14Á16]) or incomplete followup results were presented [17], and the authors, upon request, did not provide more specific data.…”
Section: Methodsmentioning
confidence: 99%
“…Transference and countertransference (emotional reactions), along with interpretations by therapists and supervisors, can show how feelings, behavior, and expressions toward them are based on parallel processes (Cassoni, 2007;Clarkson, 1991;Cornell & Landaiche, 2006). The research of Safran, Muran, Samstag, and Winston (2005) found that when a poor therapeutic alliance during the therapy process is taken to supervision, a more collaborative examination there resulted in less blaming of the client. Hill and Knox's (2009, p. 26) review of the empirical research literature on supervision and training identified that supervisors need to focus more closely on the therapist's relationship with clients through exploring the supervisor's and supervisee's modeling of interpersonal processes.…”
Section: Review Of the Supervision Literaturementioning
confidence: 99%
“…The fact that these findings cut across different therapeutic approaches with presumably different specific therapeutic techniques has led many observers to conclude that the main curative factor in virtually all types of therapy is the therapeutic relationship (e.g., Lambert and Barley 2001). Indeed, taking this view quite seriously, Muran et al (2005) have formulated a brief relational therapy model (BRT) in which the primary tasks of the treatment are to track ruptures in the therapeutic alliance and to help the patient become more aware of how he or she relates to, and implicitly negotiates and communicates with the therapist (see Safran et al 2005).…”
Section: ''The Therapeutic Alliance''mentioning
confidence: 98%